Considerations on Hannah Arendt’s understanding of history (Research, Society and Development, 2024)
This article deals with Hannah Arendt's understanding of history in the phase of reconciliation with the world, from 1952 to 1961. The main sources selected were the books The Human Condition, from 1958, and Between Past and Future, from 1961. We set ourselves the problems of "what is Arendt's understanding of history between 1952 and 1961?" and "what characteristics make up this understanding of history?". With this, we aim to "analyze Hannah Arendt's understanding of history, based on the historiographical contributions drawn from the sources". We have chosen three sets of authors that we think are interesting for discussing the subject. Firstly, Reinhart Koselleck and Walter Benjamin; secondly, Arendt's biographers; and thirdly, the critical fortune of Arendt in Brazil, especially in the field of History. Our methodological framework was made up of borrowings from the categories ausgrenzung, space of experience and horizon of expectation, theorized by Koselleck in the context of the Begriffsgeschichte (history of concepts). In addition to these, we added the stratum of experience perspective, also from a koselleckian perspective, in order to enrich our analysis. In this way, our research has led us to highlight Arendt's understanding of history as: a) the need for a new relationship with the past; b) the formation of factual matter as novelty; and c) the writing of history as a process of reifying real history into narrated history.